STUDENTS’ PERCEPTION ON THE USE OF MOVIE FOR VOCABULARY MASTERY - Michelle Tumengkol; Jenie Posumah; Nihta Liando (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study was to find out students' perceptions on the use of movie for vocabulary mastery. In this research, the researcher used questionnaires. The research method utilized by the researcher was quantitative research, and the data that have been collected were presented as numbers and total using a percentage formula. The 240 students in the 12th grade at SMA Kristen 1 Tomohon made up the population of this study. Thirty two students who responded to the questionnaire were used as the sample by the researcher. According to the study's findings, the sample of students had a lot of experience watching movies, and their responses to the questions preferred to be positive. The utilization of the movie was concluded to have been advantageous and successful for SMA Kristen 1 Tomohon students in the 12th grade. It was advised that English teachers always use a creative approach similar to what has been done before, follow technological advancements, improve what needs to be improved, and gain from every consequence in terms of results.